Wettability Gradient-Induced Diode: MXene-Engineered Membrane for Passive-Evaporative Cooling - Leqi Lei; Shuo Meng; Yifan Si; Shuo Shi; Hanbai Wu; Jieqiong Yang; Jinlian Hu (Nano-Micro Letters, 2024)
Highlights Engineering MXene into electrospun nanofibers can effectively enhance its thermal emissivity and conductance, and the unidirectional water transport of the wettability-gradient-induced-diode (WGID) membrane displayed diode-like properties with wettability gradient by tailoring the water contact angle of each single layer. The WGID membrane could achieve a cooling temperature of 1.5 °C in the “dry” state, and 7.1 °C in the “wet” state, with high emissivity of 96.40% in the MIR range, superior thermal conductivity of 0.3349 W m−1 K−1. Zero-energy-consumption for personal cooling management via multiple heat dissipation pathways, including thermal radiation, conduction, and evaporation.